Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor Dalam Upaya Meningkatkan Penerimaan Pajak Daerah Pada Kantor Samsat Maumere - Yefrianus Fernando; Henrikus Herdi; Konstatinus Pati Sanga (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This research aimed to determine and analyze Vehicle Tax revenue in increasing the local tax revenue at the One-stop Administration Services Office Maumere and to analyze the factors causing the realization of Vehicle Tax not to reach the target. This research approach was descriptive using qualitative data types. This research data were in the form ofprimary data and secondary data. The data analysis technique used was in the form of qualitative descriptive analysis techniques. The research findings showed that the real growth of motorized vehicles seemed to be increasing but the Vehicle Tax had never reached the target. The efforts taken by the local government in increasing the Vehicle Tax included creating tax support facilities in the form of building outlets in urban and rural areas, conducting direct field outreach, promoting tax payment policies, and offering One-stop Administration Services mobile to all of Sikka Regency's regions.